Anti–corrosive siloxane coatings for improved long–term performance of supercapacitors with an aqueous electrolyte. (10th March 2021) - Wojciechowski, Jarosław; Kolanowski, Łukasz; Graś, Małgorzata; Szubert, Karol; Bund, Andreas; Fic, Krzysztof; Lota, Grzegorz
Abstract: This paper reports on the impact that the corrosion of the stainless steel current collectors has on the performance fade of a symmetric, carbon/carbon electrochemical capacitor, operating with an aqueous electrolyte (1 M Na2 SO4 ). The results obtained by applying electrochemical ageing protocols (voltage–holding tests) confirm that the current collector of the positive electrode undergoes tremendous degradation during 200 h in the charged state. To prevent the detrimental impact of the corrosion, a hydrophobic siloxane coating has been successfully applied. In the case of siloxane–protected current collectors that are subjected to identical ageing protocols, no significant deterioration in the electrochemical capacitor performance was observed. The siloxane coating reduces the electrochemical corrosion rate of 316 L stainless steel significantly, as the potentiodynamic polarization tests and the electrochemical impedance spectroscopy results show. The presence of the coating is demonstrated by the water contact angle measurements, atomic force microscopy and energy–dispersive X–ray spectroscopy analysis. Graphical abstract: Image, graphical abstract